2019
DOI: 10.3390/photonics6020058
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamics of Exclusive Excited-State Emission Quantum Dot Lasers Under Optical Injection

Abstract: We numerically investigate the nonlinear dynamic properties of an exclusive excited-state (ES) emission quantum dot (QD) laser under optical injection. The results show that, under suitable injection parameters, the ES-QD laser can exhibit rich nonlinear dynamical behaviors, such as injection locking (IL), period one (P1), period two (P2), multi-period (MP), and chaotic pulsation (CP). Through mapping these dynamic states in the parameter space of the frequency detuning and the injection coefficient, it can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Furthermore, some theoretical and experimental simulations show that the nonlinear dynamics behavior of SLs can be influenced by an external perturbation such as optical feedback [38][39][40], optoelectronic feedback [41][42][43][44], mutual coupling [45][46][47], and optical injection [12,[48][49][50]. Then the regions of more complex dynamics can be expanded with these external perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some theoretical and experimental simulations show that the nonlinear dynamics behavior of SLs can be influenced by an external perturbation such as optical feedback [38][39][40], optoelectronic feedback [41][42][43][44], mutual coupling [45][46][47], and optical injection [12,[48][49][50]. Then the regions of more complex dynamics can be expanded with these external perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier work revealed that the ES-QD laser can exhibit rich nonlinear dynamic behaviors under external optical injection, in which a large area of P1 oscillation appears in the positive frequency detuning region. [36] Based on this work, we have studied the distributions of the P1 microwave frequency and microwave intensity within this region, and employed optical feedback technology to stabilize the microwave signal and narrow the microwave linewidth.…”
Section: Introductionmentioning
confidence: 99%
“…[35] Besides, two excitonic energy levels of the GS and the ES are considered in the QD ensemble, and the stimulated emission only occurs in ES in this system. [19,36] To this end, the carriers are first injected into the reservoir (RS) before being captured to the ES within the time τ RS ES , and then they will relax into the GS within the time τ ES GS . [37] On the other hand, several carriers will escape from GS (ES) within the time τ GS ES (τ ES RS ) due to the thermal excitations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations